Wilkie's syndrome - An unusual presentation in an elderly female - Lakshmi Venkata Simhachalam Kutikuppala; M V Sathvika; T Uma Maheswara Rao; Hemanth Kumar Chowdary (Wolters Kluwer Medknow Publications, 2020)
Wilkie's syndrome, also called as superior mesenteric artery syndrome (SMAS), is an extremely uncommon condition, which is evident in only 0.1%-0.3% of the population. This is a case of a 55-year-old female who presented to our hospital complaining of abdominal discomfort for 20 days, vomiting of two episodes per day for 20 days, constipation for 20 days, decreased appetite for 20 days, and significant weight loss. After further examination and investigations, it was diagnosed as SMAS and managed surgically through duodeno-jejunostomy followed by duodeno-jejunal and jejuno-jejunal anastomosis. She was later followed through conservative management and discharged from the hospital in a stable condition.